Islamic values in contemporary Indonesian poetry: A qualitative content analysis of Yuslidar’s Suara Hati Seorang Ibu - Pheni Hastuti; Heny Friantary; Vebbi Andra (Yayasan Darussalam Bengkulu, 2024)
This study examines how Islamic religious values are aesthetically articulated in Yuslidar’s poetry collection Suara Hati Seorang Ibu and how those articulations inform literary pedagogy in Indonesia. Using a qualitative content analysis with a deductive–inductive logic, we analyzed the entire volume and operationalized a codebook grounded in four macro categories monotheism (tawhid), ethical conduct (akhlak), doctrinal belief (aqidah), and Islamic jurisprudence (fiqh). Two analysts independently coded minimal textual “value instances” (word, line, couplet, stanza, paratext), resolved discrepancies through negotiated consensus, and maintained an audit trail of codebook versions and analytic memos. We identified 99 instances: tawhid 47 (47.5%; faith in God 36, taqwa 7, repentance 4), akhlak 44 (44.4%; sincerity 14, gratitude 9, patience 6, reliance on God 5, discipline 4, trust/responsibility 4, humility 2), aqidah 3 (3.0%; revealed matters), and fiqh 5 (5.1%; lawful 2, prohibited 3). The results reveal a devotional core faith operationalized ethically through sincerity and gratitude, with patience and reliance functioning as coping scripts under uncertainty; jurisprudential and doctrinal markers appear sparingly as boundary-setting closures that stabilize interpretation. These patterns converge with evidence that poetry supports character formation yet extend prior work by offering a single-author, frequency-based “value cartography” that surfaces how a maternal voice localizes virtues across domestic, civic, and pandemic-era scenes. The findings imply actionable designs for literature and Islamic-studies classrooms: structuring “value constellations” into close reading, dialogic inquiry, and reflective writing assessed with analytic rubrics, while future research should triangulate text analysis with classroom interventions and formal reliability metrics to evaluate effects on character and socio-emotional competencies.